The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/15389588.2017.1329535
|View full text |Cite
|
Sign up to set email alerts
|

Considering built environment and spatial correlation in modeling pedestrian injury severity

Abstract: This study emphasizes the need for thinking about traffic calming measures, illumination solutions, road maintenance programs, and speed limit reductions. Moreover, this study emphasizes the role of the built environment, because shopping areas, residential areas, and walking traffic density are positively related to a reduction in pedestrian injury severity. Often, these areas have in common a larger pedestrian mass that is more likely to make other road users more aware and attentive, whereas the same does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 28 publications
6
20
1
Order By: Relevance
“…Research on the severity of pedestrian-vehicle crashes has been ongoing for many years in multiple countries [1][2][3][8][9][10]13,14,[16][17][18][19][20][21][22][23]. Many studies have identified factors that affect the severity of pedestrian injuries, including the personal characteristics of pedestrians and drivers, temporal characteristics, and aspects of the built environment, such as road characteristics and land use.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on the severity of pedestrian-vehicle crashes has been ongoing for many years in multiple countries [1][2][3][8][9][10]13,14,[16][17][18][19][20][21][22][23]. Many studies have identified factors that affect the severity of pedestrian injuries, including the personal characteristics of pedestrians and drivers, temporal characteristics, and aspects of the built environment, such as road characteristics and land use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, Pour-Rouholamin and Zhou [10], Guo et al [22], and Choe et al [28] find that young drivers, who are relatively inexperienced in driving, have a higher risk of fatality and can cause serious accidents. In addition, studies focusing on drivers' gender find statistically significant differences between male drivers and female drivers in relation to injury severity [1,18,19,21,23].…”
Section: Accident Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower speed roads are associated with a reduced risk of pedestrian motor vehicle collision (PMVC) as well as less severe PMVC injuries [5]. A comprehensive literature review that examined pedestrian fatality risk as a function of car impact speed showed that for every 1.6 km/h reduction in speed, PMVC frequency was reduced by 5% [6].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of impact speed and pedestrian fatality risk supports setting speed limits of 30-40 km/h for high pedestrian activity areas as the risk of a fatality reaches 5% at an estimated impact speed of 30 km/h [8]. Although many studies report a reduction in severe PMVC injuries and crash risk after lowering speed limits, speed limit reductions have not been well studied using controlled quasi experimental designs [5,9,10].…”
Section: Introductionmentioning
confidence: 99%